2010
DOI: 10.1590/s0101-31222010000100014
|View full text |Cite
|
Sign up to set email alerts
|

Teste de condutividade elétrica para avaliação da qualidade fisiológica de sementes de azevém (Lolium multiflorum L.)

Abstract: RESUMO -O teste de condutividade elétrica tem potencial para ser empregado no controle de qualidade pelas empresas produtoras de sementes, no entanto há fatores que podem afetar os resultados obtidos. O objetivo do trabalho foi avaliar o efeito do número de sementes, volume de água e o tempo de embebição na condutividade elétrica da solução, para avaliação do vigor em sementes de azevém. O experimento foi conduzido utilizando-se quatro lotes de sementes de azevém. O teste foi realizado à temperatura de 25 ºC, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 10 publications
1
10
1
5
Order By: Relevance
“…The correlation of data from a vigor test with seedling emergence in the field is crucial to consider the test successful because it should classify the lots into different levels of vigor as close as possible to seedling emergence in the field (ARAÚJO et al, 2011;LOPES;FRANKE, 2010;MARCOS-FILHO, 2015).…”
Section: Continuationmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation of data from a vigor test with seedling emergence in the field is crucial to consider the test successful because it should classify the lots into different levels of vigor as close as possible to seedling emergence in the field (ARAÚJO et al, 2011;LOPES;FRANKE, 2010;MARCOS-FILHO, 2015).…”
Section: Continuationmentioning
confidence: 99%
“…Therefore, the tests that efficiently assess the seed physiological potential should be identified for each species, thereby enabling obtaining consistent and reproducible results (LOPES; FRANKE, 2010;MARCOS-FILHO, 2015;STEINER et al, 2011). Quality control laboratories usually perform several vigor tests simultaneously, in addition to the germination test, to classify seed lots safely into different levels of physiological quality (SOARES et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly (i.e., due to solute dilution), the 75-mL soaking volume was less efficient in distinguishing between the vigor of the two seed lots. Pereira and Martins Filho (2012) observed a similar pattern, with lower soaking volumes facilitating the discrimination of Solanum sessiliflorum seed lots with different qualities, and both Lopes and Franke (2010) and Milani et al (2012) reported that lower water volumes were more appropriate for measuring the electrical conductivity of Lolium multiflorum and Brassica napus seeds, respectively. Therefore, there appears to be a direct relationship between the seed vigor differentiation and soaking volume.…”
Section: Resultsmentioning
confidence: 83%
“…Esses testes Alguns testes de vigor podem ser realizados conjuntamente com o de germinação, a exemplo da primeira contagem de plântulas, realizada para facilitar a condução do teste de germinação, uma vez que a velocidade da germinação é uma das primeiras características a serem afetadas no processo de deterioração das sementes (COIMBRA et al, 2009;MACHADO et al, 2012;MARTINS et al, 2014). Portanto, deve-se identificar quais os testes de avaliação do potencial fisiológico são eficientes para as sementes de cada espécie, possibilitando a obtenção de resultados consistentes e reproduzíveis FRANKE, 2010;MARCOS-FILHO, 2015;STEINER et al, 2011). Os laboratórios de controle de qualidade costumam utilizar vários testes de vigor simultaneamente, além do teste de germinação, para classificar com maior segurança os lotes de sementes em diferentes níveis de qualidade fisiológica (SOARES et al, 2010).…”
Section: Introductionunclassified